Measuring the Improvement of Students’ Critical Thinking Abilities through Seamless Learning: A Quasi-Experimental Approach - Putu Satya Narayanti; Andiopenta Purba; Aat Ruchiat Nugraha (Yayasan Adra Karima Hubbi, 2024)
Background. 21st century education emphasizes the importance of developing high-level thinking skills (HOTS) for students, including analysis, evaluation and synthesis skills. Seamless learning, which integrates technology and media, becomes relevant in this context because it creates a dynamic and connected learning experience. Purpose. This research aims to measure the increase in students’ critical thinking abilities through seamless learning using quasi-experimental methods. By adopting this approach, the research seeks to provide empirical evidence about the effectiveness of seamless learning in improving students’ critical thinking abilities. Method. This research methodology takes a quantitative approach with quasi-experimental methods. Data was collected from a school in West Sumatra, with research subjects being grade 7 students. Data collection was carried out through critical thinking ability test instruments before and after the learning period. Analysis was carried out using the t-test in SPSS to compare the two groups. Results. The results of the analysis showed significant differences between the experimental and control groups, with a greater increase in critical thinking ability scores in the experimental group. The resulting t value was 0.05, with a p value of less than 0.05, indicating that the difference between the two groups did not occur by chance. This confirms that seamless learning has a positive impact in improving students’ critical thinking abilities. Conclusion. These findings highlight the success of seamless learning in improving students’ critical thinking abilities. However, this study has limitations, such as the relatively small sample size and limited duration of the intervention. Further research with larger sample sizes is recommended to deepen this understanding.